Correlation between low testosterone levels and the risk of osteoarthritis: a cross-sectional analysis of NHANES data (2011–2016) - Ning Ma; Fang Gao (BMC Musculoskeletal Disorders)
Abstract Background Osteoarthritis (OA) is a common degenerative joint disease that significantly impacts the quality of life, especially among older adults. Testosterone, a critical hormone for musculoskeletal health, has been suggested to influence OA pathogenesis. However, the relationship between low testosterone levels and OA risk remains underexplored in large, representative populations. This study aimed to investigate the association between low testosterone levels and OA risk using data from the National Health and Nutrition Examination Survey (NHANES, 2011–2016). Methods This cross-sectional analysis included 4,548 participants from NHANES, a nationally representative U.S. dataset. Testosterone levels were categorized as low or normal, with low testosterone defined as < 300 ng/dL for men and population-based cutoffs for women. The presence of OA was determined through self-reported physician diagnosis. Multivariable logistic regression models were used to examine the association between testosterone levels and OA risk, adjusting for demographic, socioeconomic, lifestyle, and clinical factors. Restricted cubic spline (RCS) analysis was conducted to evaluate non-linear relationships. Subgroup analyses were performed to assess consistency across key demographic and clinical strata. Results Among the 4,548 participants, 812 (17.9%) were diagnosed with OA. Participants with OA were older, more likely to be female, and exhibited higher rates of obesity and hyperlipidemia. In fully adjusted models, low testosterone levels were significantly associated with increased OA risk (OR, 1.22; 95% CI, 1.02–1.46; P = 0.028). RCS analysis indicated a non-linear relationship, with a steep increase in OA risk at lower testosterone levels, suggesting a threshold effect. Subgroup analyses demonstrated consistent associations across demographic and clinical groups without significant interactions. Conclusion Low testosterone levels are independently associated with an increased risk of OA in the U.S. population. These findings underscore the potential role of hormonal health in OA pathogenesis and highlight the need for longitudinal studies to clarify causal pathways. The observed non-linear relationship suggests that maintaining optimal testosterone levels may be important for joint health, and testosterone replacement therapy could be explored as a preventative strategy for individuals with testosterone deficiency.